Apocalyptic groups and socially disadvantaged contexts - P. G. R. de Villiers (Acta Theologica)
This study investigates the theory that apocalyptic texts originated in, and reflect the convictions and activities of socially disadvantaged groups on the margins of society. After a brief introduction to the nature of this understanding of apocalyptic groups, the article investigates the issue in more depth by analysing an essay on Revelation written by D.H. Lawrence as concrete example of this theory from a nonscholarly perspective, followed by various scholarly readings of apocalyptic groups. In a following section, it analyses various formal, literary, hermeneutical and topical themes questioning the validity of this approach as well as research insights that revealed major weaknesses in this understanding. The article then concludes with an investigation of material that, ironically, indicates that apocalypses generally reflect a learned hermeneutical movement wishing to discover the ongoing relevance of sacred traditions in new situations.